The Effect of Giving Aromatherapy of Roseson Reducing Pain Intensity Delivery In The 1st Time it PMB Umi Salamah In 2022 - Umi Salamah; Masluroh (Lembaga Pengembangan Kinerja Dosen, 2023)
The maternal mortality rate (MMR) in Indonesia related to pregnancy, childbirth and the puerperium is still high, although on the other hand there has been a decrease from 359 per 100,000 live births (KH) in the 2016 Indonesian Demographic and Health Survey (IDHS) to 273 per 100,000 KH in 2018.The purpose of this study was to determine the effect of giving rose aromatherapy to reducing the intensity of labor pain in the first stage of labor at PMB Umi in 2022 The research method used is a quasi-experimental method with a one group pretest-posttest design approach. Univariate and bivariate research analysis using paired sample t-test statistical tests. The results of the analysis show that the t-test value is 6.08 and the p-value is 0.000 <α 0.05, which means that there has been a significant reduction in pain intensity in the first stage of labor before and after being given rose aromatherapy. And the results of the analysis of the paired sample test before and after giving rose aromatherapy, with a t-test value of 15.96, Sig. (2-tailed)/ p-value = 0.000 < α 0.05. It can be concluded that there is a significant influence between giving rose aromatherapy to reducing the intensity of labor pain in the 1st stage of labor at PMB Umi Salamah in 2022. Health workers can use aromatherapy as an alternative way of dealing with labor pain in the first stage of labor, providing adequate information to mothers about the delivery process so that mothers have proper preparation.